2021
DOI: 10.1017/s0033291721005134
|View full text |Cite
|
Sign up to set email alerts
|

The moderation of the genetic risk for alcohol and drug use disorders in a Swedish national sample by the genetic aptitude for educational attainment

Abstract: Background Does the genetic aptitude for educational attainment (GAEA) moderate the genetic risk for alcohol use disorder (AUD) and drug use disorder (DUD)? Methods In the native Swedish population, born 1960–1980 and followed through 2017 (n = 1 862 435), the family genetic risk score (FGRS) for AUD and DUD and GAEA were calculated from, respectively, the educational attainment and risk for AUD and DUD, of 1st through 5th degree relatives from Swedish national registers. Analyses utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Fourth, the FGRS, a family phenotype-based method to assess quantitative genetic risk, has been now widely published, with prior reports demonstrating that this score is not highly sensitive to the various assumptions involved in its calculation, that the correction for cohabitation effects performs appropriately, and the method agrees well with other similar, although statistically distinct, approaches …”
Section: Discussionmentioning
confidence: 90%
“…Fourth, the FGRS, a family phenotype-based method to assess quantitative genetic risk, has been now widely published, with prior reports demonstrating that this score is not highly sensitive to the various assumptions involved in its calculation, that the correction for cohabitation effects performs appropriately, and the method agrees well with other similar, although statistically distinct, approaches …”
Section: Discussionmentioning
confidence: 90%
“…Using methods outlined previously (Kendler, Ohlsson, Sundquist, Edwards, & Sundquist, 2021; Kendler, Ohlsson, Sundquist, & Sundquist, 2021a, 2021b, 2021c, 2021d), we calculated an FGRS for AUD and MD for all individuals in our study cohort—born 1970–1990. Table S2 contains a detailed explanation of the FGRS which we summarize here.…”
Section: Methodsmentioning
confidence: 99%
“…Third, we have studied a large population cohort of cases of two disorders widely considered to be heterogeneous. We have shown that the FGRS for MD and AUD varies as a function of age of onset and number of recurrences (Kendler, Ohlsson, Bacanu, Sundquist, & Sundquist, 2022; Kendler, Ohlsson, Sundquist, & Sundquist, 2021a, 2021b, 2021c, 2021d) but this has also been shown using more traditional methods (K. S. Kendler, Gatz, Gardner, & Pedersen, 2005) and reflects more quantitative than qualitative differences among affected cases. Furthermore, we had examined, by structural equation modeling, the relationship between AUD with and without medical complications in the Swedish data and showed them to be relatively closely genetically related (Edwards, Sundquist, Sundquist, Kendler, & Larsson Lönn, 2021).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This change in the “natural order” of life events and untimely loss permanently alter the hopes and dreams parents may have had for their child 2,3 . Parental bereavement is considered distinct from other types; it is more intense when compared with the death of a sibling, mother, or father 4 . After the death of a child, parents experience a loss of identity and connection to the community, which in turn, impacts their health and well-being 5 …”
mentioning
confidence: 99%